Analytical evaluation of the dome-cylinder interface of nuclear concrete containment subjected to internal pressure and thermal load. (15th April 2018) - Wang, Shen
Highlights: A detailed study is performed for the dome-cylinder interface of concrete containments. The compatibility and internal forces at interface is investigated using nonlinear methods. A practical example is presented as the case study. Conclusion and recommendations are provided for the dome-cylinder boundary. Abstract: Nuclear concrete containment structures serve as the main line of defense to prevent escape of radioactive material during catastrophic events including the loss of coolant accident (LOCA), explosions and earthquake. In the case that such an event occurred, the containment would need to resist high internal pressure and temperature loads. This paper studies the dome-cylinder interface of concrete containments subjected to significant internal pressure and temperature load. In particular, the compatibility at geometry discontinuity and internal forces as a result of displacement discrepancy is investigated using nonlinear mechanics based formulas. A practical example of concrete containment is presented as a case study. The study reveals that the current practice in nuclear concrete containment design may significantly underestimate the stress at the dome-cylinder interface, which would lead to insufficient design. The presented approach provides an easy to use tool to assess the dome-cylinder interface of a concrete containment.